2019
DOI: 10.1002/lsm.23122
|View full text |Cite
|
Sign up to set email alerts
|

Image‐Guided Ablation of Dental Calculus From Root Surfaces Using a DPSS Er:YAG Laser

Abstract: Background and Objectives Recent studies have demonstrated that near‐infrared (IR) imaging can be used to acquire high‐contrast images of root caries and calculus on the root surfaces of extracted teeth at wavelengths longer than 1450 nm. The purpose of this study was to determine if image‐guided laser ablation can be used to selectively remove calculus from tooth surfaces with minimal damage to the underlying sound cementum and dentin. Materials and Methods In this study, sequential near‐IR images at 1500–170… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Damage to the enamel makes it more susceptible to bacterial plaque accumulation. Radiation can also affect the physical properties of bacterial plaque that adheres to teeth [29]. Certain doses of radiation can make plaque more "sticky" to the tooth surface, making it more difficult to effectively remove by brushing or maintaining oral hygiene.…”
Section: Resultsmentioning
confidence: 99%
“…Damage to the enamel makes it more susceptible to bacterial plaque accumulation. Radiation can also affect the physical properties of bacterial plaque that adheres to teeth [29]. Certain doses of radiation can make plaque more "sticky" to the tooth surface, making it more difficult to effectively remove by brushing or maintaining oral hygiene.…”
Section: Resultsmentioning
confidence: 99%
“…SWIR and OCT images may be useful to help guide caries removal by more accurately showing the lateral spread of caries lesions below the enamel. Other studies have shown that SWIR and OCT images can be used to help guide the selective removal of calculus from root surfaces [55]. Serial SWIR images have been used to facilitate the selective removal of small occlusal lesions confined to the enamel [56].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting that recently published studies with novel laser systems [32–34] suggest that laser ablation may be used also as an alternative to standard mechanical instrumentation in order to reduce generated debris and smear layer.…”
Section: Discussionmentioning
confidence: 99%